Cell Wall-Associated Virulence Factors Contribute to Increased Resilience of Old Cryptococcus neoformans Cells - Orner, Erika P.; Bhattacharya, Somanon; Kalenja, Klea; Hayden, Danielle; Del Poeta, Maurizio; Fries, Bettina C. (Frontiers in Microbiology, 2019)
As Cryptococcus neoformans mother cells generationally age, their cell walls become thicker and cell-wall associated virulence factors are upregulated. Antiphagocytic protein 1 (App1), and laccase enzymes (Lac1 and Lac2) are virulence factors known to contribute to virulence of C. neoformans during infection through inhibition of phagocytic uptake and melanization. Here we show that these cell-wall-associated proteins are not only significantly upregulated in old C. neoformans cells, but also that their upregulation likely contributes to the increased resistance to antifungal and host-mediated killing during infection and to the subsequent accumulation of old cells. We found that old cells melanize to a greater extent than younger cells and as a consequence, old melanized cells are more resistant to killing by amphotericin B compared to young melanized cells. A decrease in melanization of old lacΔ mutants lead to a decrease in old-cell resilience, indicating that age-related melanization is contributing to the overall resilience of older cells and is being mediated by laccase genes. Additionally, we found that older cells are more resistant to macrophage phagocytosis, but this resistance is lost when APP1 is knocked out, indicating that upregulation of APP1 in older cells is in part responsible for their increased resistance to phagocytosis by macrophages. Finally, infections with old cells in the Galleria mellonella model support our conclusions, as loss of the APP1, LAC1, and LAC2 gene ablates the enhanced virulence of old cells, indicating their importance in age-dependent resilience.